2022
DOI: 10.1093/jxb/erac517
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of three-dimensional chromatin architecture inMedicago truncatulaunder phosphorus deficiency

Abstract: Emerging evidence reveals that the three-dimensional (3D) chromatin architecture plays a key regulatory role in various biological processes of plants. However, information on the 3D chromatin architecture of legume model plant Medicago truncatula and its potential roles in the regulation of response to mineral nutrient deficiency are very limited. Using Hi-C sequencing, we identified the 3D genome structure of M. truncatula in terms of A/B compartments, topologically associated domains (TADs) and chromatin lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Significantly higher gene expression levels were found in the A compartments under both low-and normal-Pi conditions than in the B compartments (Figure 2b). Certain earlier investigations have also revealed parallel outcomes in maize and other plant species, indicating notably elevated gene expression levels in A compartments compared to B compartments (Dong et al, 2017(Dong et al, , 2018Wang et al, 2018Wang et al, , 2023. Similarly, levels of mCHH, mCHG, and mCG were significantly higher in compartments A than in B, with the most drastic decrease and the largest range in difference between the compartments in mCHH (Figure 2a,b); mCG and mCHG levels differed significantly between compartments A and B, but the range was small (Figure 2b).…”
Section: Gene Expression and Methylation Patterns In The A/b Compartm...mentioning
confidence: 80%
See 1 more Smart Citation
“…Significantly higher gene expression levels were found in the A compartments under both low-and normal-Pi conditions than in the B compartments (Figure 2b). Certain earlier investigations have also revealed parallel outcomes in maize and other plant species, indicating notably elevated gene expression levels in A compartments compared to B compartments (Dong et al, 2017(Dong et al, , 2018Wang et al, 2018Wang et al, , 2023. Similarly, levels of mCHH, mCHG, and mCG were significantly higher in compartments A than in B, with the most drastic decrease and the largest range in difference between the compartments in mCHH (Figure 2a,b); mCG and mCHG levels differed significantly between compartments A and B, but the range was small (Figure 2b).…”
Section: Gene Expression and Methylation Patterns In The A/b Compartm...mentioning
confidence: 80%
“…In this study, the partition of compartments A and B remained unchanged between low‐ and normal‐Pi conditions, with no inverted regions between the compartments observed under these two nutritional conditions (Figure 2a; Figure S1). In a recent study conducted in Medicago truncatula , it was demonstrated that the partitioning of A/B compartments remained consistent under both low and normal phosphorus conditions, with the exception of a few minor intervals that exhibited a shift between these two conditions (Wang et al., 2023).…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, the functional role of the ABCG40 transporter is implicated in importing ABA to stomatal cells and drought stress [ 112 ]. In Medicago, the overexpression of the Chr6g0452171 gene that encodes ABC transporter B family protein enriched the histone mark under phosphorus deficiency (PD) and their possible role in PD-induced root system architecture (RSA) remodeling has been reported [ 113 ].…”
Section: Discussionmentioning
confidence: 99%